Universalism: Global Evidence - Cappelen, Alexander W.; Enke, Benjamin; Tungodden, Bertil (American Economic Review, 2025)
This paper leverages nationally representative surveys across 60 countries and 64,000 respondents to present novel stylized facts about the relationship-specific nature of altruism. Across individuals, universalist preferences systematically vary with demographics such as age and religiosity and are predictive of many left-wing political views, albeit in culturally highly heterogeneous ways. Across countries, universalism is strongly linked to a broader radius of trust. Looking at origins, universalism varies with the economic, political, and religious organization of societies in ways that are consistent with the idea that the scope of altruism is partly shaped by economic incentives and democracy. (JEL D12, D64, D72, Z12, Z13)